THE DIFFERENCE OF TRIGONOMETRY LEARNING OUTCOMES BY COMBINING THE USE OF GOOGLE CLASSROOM, WHATSAPP GROUP, AND YOUTUBE BASED ON STUDENTS PARTICIPATION DURING THE PANDEMIC OF COVID-19 - Gunadi, Farid; Rosyadi, Rosyadi (PRISMA, 2022)
The pandemic Covid-19 impacted the learning activity, especially Mathematics learning in trigonometry. Trigonometry is considered as challenging material. The teacher uses many ICT products to help the students understand the trigonometry material; Google Classroom, WhatsApp, and Youtube (GC+WAG+YT). However, the low student participation in those applications becomes a new challenge. Therefore, this study aims to analyze the learning outcome difference by combining Google Classroom, WhatsApp, and Youtube in learning trigonometry material. This study will focus on how the students participate actively in the learning process. This study employed an experimental design by taking the sample randomly. One class is given the treatment of combining the three applications; Google Classroom, WhatsApp, and Youtube. This study used a test as the instrument to collect the data. The data were then analyzed using U-Mann Whitney. This study reported that the students who participated actively showed better learning outcomes in trigonometry material than those who participated passively. Thus, the teacher is suggested to create a more effective and efficient learning outcome in any conditions, particularly during the Pandemic Covid-19.